The dielectric spectroscopy and surface morphology studies in a new conjugated polymer poly(benzobisoxazole-2,6-diylvlnylene) - Yakuphanoğlu, Fahrettin; Okutan, M; Zhuang, QX; Han, ZW (Elsevier, 2005)
The surface morphology and dielectric properties of a new conjugated polymer poly(benzobisoxazole-2,6-diylvinylene) (PBOV) have been investigated by atomic force microscopy (AFM) and dielectric spectroscopy (DS). The dielectric parameters of the polymer were calculated. An increase in the dielectric constant is observed due to interfacial polarization. AFM photographs indicate that morphology of surface has regular structure. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: polymer; dielectric loss and relaxation; permittivity (dielectric function)